Analisis Resiko Kebijakan Harga Eceran Tertinggi (HET) Obat di Tengah Melemahnya Rupiah dan Konflik Geopolitik Global - Iin Riana; Khofifah Ali Safitri; Mey Apriansyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Significantly, only 27% of companies source their materials domestically (Wahyudi et al., 2023). Given the current global geopolitical conflicts, such as the maritime crisis in the Red Sea corridor and political tensions in the Middle East, these factors are causing global supply chain disruptions, container shortages, and surging energy prices—all of which directly contribute to skyrocketing international freight costs. These disruptions will significantly impact the escalation of the Cost of Goods Manufactured (COGM) for pharmaceutical factories, which will ultimately lead to two major risks: an increase in drug prices and the Maximum Retail Price (MRP) of drugs, as well as drug shortages due to limited production materials. This study employs the Systematic Literature Review (SLR) method to identify, evaluate, and interpret all relevant scientific evidence regarding the risk analysis of the Maximum Retail Price (MRP) policy for medicines amid the weakening of the rupiah and global geopolitical conflicts. The Maximum Retail Price (MRP) policy for medicines cannot be rigidly enforced amid the weakening of the rupiah and global geopolitical conflicts.